If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1(7n + 9) = 0 Reorder the terms: 1 + -1(9 + 7n) = 0 1 + (9 * -1 + 7n * -1) = 0 1 + (-9 + -7n) = 0 Combine like terms: 1 + -9 = -8 -8 + -7n = 0 Solving -8 + -7n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -7n = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -7n = 0 + 8 -7n = 0 + 8 Combine like terms: 0 + 8 = 8 -7n = 8 Divide each side by '-7'. n = -1.142857143 Simplifying n = -1.142857143
| 2x+3x-5=8 | | 4m^2+4m-1=0 | | 24vw^5x^3+30v^8w^9=0 | | 7[x-3(2y-7x)]= | | 12x+6=0+3x | | (x-0.5)(x-0.5)-1.561=0 | | a(2-a)= | | y-9(-5.5)=3 | | 10/280 | | 2-4=r | | 6+3(3.4)= | | -2(x+5)+4=3(x+4)+1 | | -1/6y-(y-4/7)=1/42(y-8) | | 3x*(4/9) | | 20*1/2= | | -(x-4)=3x-20 | | -4.8+7(-1-3(25))=3(-1-7(25)) | | X[n]=2u[-n] | | -4.8+7(-1.2-3(36))=3(-1.2-7(36)) | | 5x(4x+6)=-4 | | -4.8+7(1.2-3(36))=3(1.2-7(36)) | | 4x+(x+3)+2(x+4)= | | ln(x)/ln(y) | | -4.8+7(1-3(25))=3(1-7(25)) | | (x-0.5)(x-0.5)+1.561=0 | | 2p^2x^2+pqx-15q^2=0 | | 5x-8=28-4x | | 5x-8=28-4 | | 56a(3+x-2b)=c(dx-2) | | x^4-6x^3+27x=0 | | (6n^4-2n+5n)+(2n+6n^4+4n^2)= | | .96+x=.16(12+x) |